2017
DOI: 10.1093/gbe/evx076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Host–Symbiont and Free-Living Oceanobacillus Species

Abstract: Survival in a given environment requires specific functions, so genomic variation is anticipated within in individual taxonomic groups that exhibit a large diversity in lifestyles. In this study, we sequence and assemble the genome of Oceanobacillus faecalis strain HM6, a resident of the human gut. Using the genus Oceanobacillus and the HM6 draft genome sequence, we explore the functional requirements for survival in a symbiotic arrangement within the human gut, in contrast to free living in the environment. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Functional annotation revealed a gene (OG_1965) coding for an ABC transporter permease protein (COG0577). Consistent with its distribution in HA strains in subclade III-b, it has been reported that it is associated with isolates from human gut compared with free-living environments in Oceanobacillus species [86]. However, the potential functions of most genes detected in the association with HA/NHA habitats remain unclear.…”
Section: High Level Of Homologous Recombination In M Luteus Speciesmentioning
confidence: 71%
“…Functional annotation revealed a gene (OG_1965) coding for an ABC transporter permease protein (COG0577). Consistent with its distribution in HA strains in subclade III-b, it has been reported that it is associated with isolates from human gut compared with free-living environments in Oceanobacillus species [86]. However, the potential functions of most genes detected in the association with HA/NHA habitats remain unclear.…”
Section: High Level Of Homologous Recombination In M Luteus Speciesmentioning
confidence: 71%
“…These studies explain the abundance of Proteobacteria, Actinobacteria, Gemmatimonadetes , and Bacteroidetes in the studied ecosystem. Evolution of novel genetic features is a key to their successful survival in a changing environment (Gupta et al, 2017 ; Kumar Mondal et al, 2017 ). These saline microorganisms could have evolved salt stress tolerant genetic machinery to adapt and survive under salt induced osmotic stresses (Meena et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial diversity within the human gut plays a significant role in human health, physiology and tissue development 16 . They do so by their ability to counter numerous environmental stresses such as low pH, bile acids, elevated osmolarity, iron limitation, insufficient nutrient availability and host immune factors 17 19 . These physiological mechanisms which cumulatively resist rapid changes in the gastrointestinal environment are crucial for their successful colonization 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…They do so by their ability to counter numerous environmental stresses such as low pH, bile acids, elevated osmolarity, iron limitation, insufficient nutrient availability and host immune factors 17 19 . These physiological mechanisms which cumulatively resist rapid changes in the gastrointestinal environment are crucial for their successful colonization 19 , 20 . Efforts were made to elucidate salt tolerance genes from human gut microbiome and following salt tolerance genes including brp/blh, galE, murB , mazG were identified 21 23 .…”
Section: Introductionmentioning
confidence: 99%